A Study of Transportation of Timber by Long Distance Conveyor Lasso-3S in West Bengal - Mitra, S. K.; Sood, K. G. (Indian Forester, 1978)
The valuable inaccessible forests of North Bengal which virtually remained unex ploited over centuries are opened up now due to the introductiou of elaborate and efficient complex of aerial transportation units like the Lasso-3S. Long distance conveyor and Hinteregger all terrain skyline crane. The efficiency and cost studies were conducted on the Lasso-3S. Long distance conveyor working in Dhaper forests of Kalimpong Forest Division. The Lasso-3S ropeway is permanently installed over a span of 4.02 km and are feeded by two Hinteregger all terrain skyline cranes. The coat of aerial transportation of timber over the distance in calculated and found to be Rs. 93.34 per m3. It is observed that there is still a scope of increasing the efficiency of the machine by 23.43% which will ultimately reduce the coat of transportation to Rs. 46.67 per m3.